Implementation of International Standards for Determining an Efficient Civil Law Remedy by a National Court - Potapenko, Andrii V.; Pylypenko, Svitlana A.; Korolenko, Vitalii M.; Melnyk, Iryna S. (International Journal of Criminology and Sociology, 2021)
The article is devoted to studying the effectiveness of protection of violated, unrecognised or disputed rights, freedoms or interests of individuals, rights and interests of legal entities, the interests of the state in civil proceedings. The purpose of the article is to study how to implement international standards for determining an efficient civil law remedy by the court: (based on the case-law of the European Court of Human Rights and national case law). Clarification of the essence of novels of substantive and procedural law in determining the court’s effective way to protect private law as the final judicial procedure of the right to judicial protection was by comparative law, methods of analysis, modelling and synthesis with the implementation of related elements of classical methods of protection and reception of the best acquisitions of legal systems of foreign countries, norms of the Convention of the case-law of the European Court of Human Rights (from now on – ECtHR). The dialectical method of cognition and the qualitative empirical method were also the main ones, by means of which the legal nature of the category "efficiency" and "determination by the court of an effective way of protection of private law and interest" were clarified.